The state of information in 2022: news about documentation, libraries, internet, digital content and scientific communication - Baiget, Tomàs (Anuario ThinkEPI, 2023)
Compilation of the main Spanish and world events and news produced during 2022 about documentation, libraries, internet, digital content and scientific communication.
Keywords: News; Ephemeris; Anniversaries; Information; Documentation; Libraries; Databases; Journals; Books; Indicators; Social networks; Information sources; Communication